Menyelami Makna dan Filosofis Budaya Tumpeng sebagai Simbol Identitas Kearifan Lokal Bagi Masyarakat - Pranoto, Damianus Suryo (Sahabat Publikasi, 2024)
The focus of this research is on the meaning of cultural and philosophical purity of tumpeng for the people of Kalisongo as an identity of local wisdom in cultural diversity. For the people of Kalisongo, tumpeng culture is a formal rite of thanksgiving that is held once a year. So, the author in this study wants to elaborate the meaning and philosophy of tumpeng in Kalisongo society. This reveals that tumpeng culture is a great thanksgiving because all families are also present to thank God for all the fortune and results received in their lives every day. Tumpeng culture for the Kalisongo people has become a local tradition that is carried out formally. That tumpeng culture is a means to give thanks to others and God who has shared abundant fortune and results. So in this culture contains several values, namely the value of human dignity, respect, kinship, solidarity, and social values. The purpose of this study also elaborates on understanding how the Kalisongo people interpret the cultural and philosophical purity of tumpeng as a distinctiveness for them to build relationships with others and God.